2017
DOI: 10.1590/s1679-45082017ao3871
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety: knowledge between multiprofessional residents

Abstract: Objective To assess the knowledge of multiprofesional residents in health about the security of the patient theme.Methods Cross-sectional study, quantitative, developed with graduate courses/residence specialties of health in a public university of Paraná, Brazil. Participants (n=78) answered a questionnaire containing nine objective questions related to patient safety. Data were analyzed using descriptive statistics, in proportion measures. The minimum 75% of correct answers was considered the cutoff for posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
3
8
1
8
Order By: Relevance
“…The present study showed that the nurses' level of good knowledge towards patient safety was 58.7% (n = 101, [95% CI; 51.7, 66.7]). The present study finding was lower when compared with a study conducted in Public University of Paraná, Brazil, which reported the knowledge of nurses' towards patient safety as 89.8% [29]. The variation might be due to that the differences in socio-economic characteristics.…”
Section: Knowledge Towards Patient Safetycontrasting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that the nurses' level of good knowledge towards patient safety was 58.7% (n = 101, [95% CI; 51.7, 66.7]). The present study finding was lower when compared with a study conducted in Public University of Paraná, Brazil, which reported the knowledge of nurses' towards patient safety as 89.8% [29]. The variation might be due to that the differences in socio-economic characteristics.…”
Section: Knowledge Towards Patient Safetycontrasting
confidence: 94%
“…Good knowledge. When nurses respond the mean or above the mean score on knowledge questions concerning to patient safety [28][29][30][31].…”
Section: Operational Definitionsmentioning
confidence: 99%
“…That study stated that a study in UK concluded that medical students had little knowledge of how to report errors and also another multi-institutional survey demonstrated that knowledge levels are limited across different medical degrees and specialties. Also, findings of the study conducted by Brasaite et al in three multi-disciplinary hospitals in Western Lithuania showed that health care professionals had low levels of safety knowledge [16] were in accordance with Oliveira et al's study conducted in a public university of Paraná, Brazil who stated that knowledge of patient safety among multi-professional residents was borderline satisfactory [18]. In a study conducted in Iran, 73% of students had negative opinions about "medical error reporting" [19].…”
Section: Discussionsupporting
confidence: 61%
“…Acredita-se que a Resolução do COFEN 0545/2017, que trata da obrigatoriedade do uso do carimbo pelos profissionais de enfermagem, poderá contribuir para melhorar a identificação correta do profissional (6) . (13,14) . (16) .…”
Section: Introductionunclassified